Teaching transformation : transcultural classroom dialogues - Keating, AnaLouise, 1961- (Palgrave Macmillan, 2007)
Drawing on indigenous belief systems and recent work in critical "race" studies and multicultural-feminist theory, Keating provides detailed step-by-step suggestions, based on her own teaching experiences, designed to anticipate students resistance to social-justice issues and encourage them to change. She offers a holistic approach to theory and practice